Clinico-laboratory profile of central nervous system infection by scrub typhus at a tertiary care hospital - Jha, Ruchi; Jaiswal, Anil Kumar (International Journal of Contemporary Pediatrics, 2019)
Background: Scrub typhus is an emerging epidemic in India. Its course can be complicated by involvement of Respiratory system, cardiovascular system, gastrointestinal system and central nervous system. Central nervous system involvement can lead to major morbidity and mortality. Methods: It is an observational study conducted in the Department of Pediatrics, Patna Medical College and Hospital, Patna from January 2016 to August 2018. All cases of AES who were serologically proven to be due to scrub typhus were clinically examined, signs and symptoms were noted, and complete blood counts were done. Lumbar puncture was done, and CSF was sent for analysis of cells, sugar and protein, IgM for scrub typhus in CSF, gram staining and CSF culture. Results: Seventy-eight cases were tested positive for scrub typhus. Incidence of scrub typhus among AES cases was 19.4% in the study. Among cases of Scrub typhus, a male predominance and sex ratio was 1.68. Age at presentation ranged from 2 months to 12 years with a mean age of 7.28 years. Most of the cases were seen in the months of September and October with a mini peak in the month of March. Fever and Altered consciousness were present in all the cases. Among laboratory investigations, thrombocytopenia was the most common feature followed by raised Transaminases. CSF Analysis shows mildly increased cell count with lymphocytic predominance and presence of few polymorphs, sugar mildly decreased, and protein mildly raised. Conclusions: Scrub typhus is an important causative agent of AES in the Eastern parts of India. It should be suspected in cases which present as AES with symptoms of hepatosplenomegaly, thrombocytopenia, and elevated liver enzymes in addition to dengue encephalitis which forms its close differential.